? Onsuiwer mensbeskouing, kenteorie en wetenskapsleer in die Synopsis Purioris Theologiae (1625): ? Christelik-filosofiese verkenning - van der Walt, B. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2011)
This article provides from the perspective of a Reformational philosophy a critical analysis of the view of the human being, theory of knowledge and the relationship between philosophy and theology of the Synopsis Purioris Theologiae (1625), the dogmatics textbook which was written upon request of the Synod of Dordt (1618-1619). The article is a follow-up on the previous article in this journal which could only discuss the ontological presuppositions of the Synopsis (its views on God, law and cosmos). The introduction (1) therefore, first gives a brief summary of the results of the preceding article, before it provides a short preview of what will follow in the present contribution. The first main section (2) reviews different facets of the anthropology of the Synopsis: its dicho tomistic nature, the human being as God’s image, its creationism and the immortality and functions of the soul. Regarding its theory of knowledge (main section 3) the emphasis falls on its semi-empiricism as well as its idea of illumination. Next (part 4) follows an exposition of the relation between reason and faith. The last main section (5) offers an explanation, first of the distinction between archetypical and ectypical theology, followed by a detailed discussion of the distinction in the Synopsis between natural and supernatural theology. The field of investigation, proof of God’s existence, necessity and defects of natural theology are explored in more detail. In a conclusion (6) attention is asked for the continued reformation of the Reformed theological heritage of the Synopsis.